Functional mobility and dynamic postural control predict overhead handball throwing performance in elite female team handball players - Eriksrud, O.; Sæland, F. O.; Federolf, P. A.; Cabri, J. (Journal of Sports Science & Medicine, 2019)
The relationship between dynamic postural control, functional mobility and team handball throwing performance, velocity and accuracy, is largely unknown. The hand reach star excursion balance test (HSEBT) is a full kinetic chain assessment tool of these factors. Specifically, L135 and R135 (extension) reaches elicit joint movement combinations similar to the cocking and acceleration phase, while the L45 and R45 (flexion) reaches elicit joint movement combinations similar to the follow-through. The purpose of this study was to determine if specific HSEBT reach measures correlate with team handball throwing performance. Eleven elite female team handball players (21.7 ± 1.8 years; 71.3 ± 9.6 kg; 1.75 ± 0.07 m) executed selected HSEBT reaches before performing five valid step-up overhead throws (1x1m target) from which throwing velocity (motion capture) and accuracy (mean radial error) were quantified. Significant relationships between HSEBT measures and mean radial error, but not throwing velocity were established. Specifically, extension composite scores (L135+R135) for the dominant (150.7 ± 17.4cm) and non-dominant foot (148.1 ± 17.5 cm) were correlated with mean radial error (p < 0.05). Also, specific reaches on the dominant (L135: 87.4 ± 5.6 cm; R135: 63.4 ± 11.8 cm) and non-dominant (R135: 87.0 ± 6.1 cm) foot were correlated with throwing error (p < 0.05). The lack of significant findings to throwing velocity might be due to a ceiling effect of both L135 and R135 and of throwing velocity. We conclude that while there may be other reasons for handball players to train and test functional mobility and dynamic postural control as measured in the HSEBT, no beneficial effect on throwing performance should be expected in an elite group of handball players.